O JORNAL COMO ELEMENTO DE TRANSFIGURAÇÃO DA HISTÓRIA EM O ANO DA MORTE DE RICARDO REIS DE SARAMAGO - Roani, Gerson Luiz (Revista Letras, 2003)
Este artigo investiga o diálogo entre a História e a Literatura no romance O Ano da Morte de Ricardo Reis de José Saramago. Nessa obra, vislumbra-se uma atitude inovadora e radical de interlocução com a História, que não se limita a uma mera representação de acontecimentos do passado português. Saramago investe no jogo do fingimento pessoano, inventando para Ricardo Reis um cotidiano e uma queda na conturbada História européia de 1936, que o poeta modernista não poderia prever para o seu mais clássico heterônimo. O discurso ficcional assume uma função restauradora, preenchendo vazios, lacunas e os silêncios do discurso historiográfico. Nesse processo, um dos recursos romanescos utilizados para a transfiguração da História consiste na inserção, na trama narrativa, de textos jornalísticos de 1936, que focalizam a situação histórica portuguesa e européia, nesse ano crucial, em que se consolidaram os regimes totalitários de índole fascista. O aproveitamento desses fragmentos da imprensa portuguesa proporciona uma minuciosa recosntituição das circunstâncias sociais, políticas e históricas de Portugal, criando uma atmosfera cotidiana que bem poderia ser a experimentada por Ricardo Reis, em 1936. Abstract The purpose of this paper is to carry out research on History and Literature in the novel O ano da morte de Ricardo Reis (translated as The year of the death of Ricardo Reis) by Portuguese writer José Saramago. The work stands out by its new and radical approach of a dialogue with History, but which is not limited to a mere representation of Portuguese past events. In Saramagos novel, the latter is revisited through the fictional recreation of one of his heteronyms, Ricardo Reis. The author probes into Pessoas play of pretence, inventing a daily routine for Ricardo Reis and plunges into the 1936 disturbances of European History, which the modernist poet could not have foreseen for his most classic heteronym. By giving Ricardo Reis an existence within new fictional parameters, the novel questions the validity of the guiding motto of this fictional figures attitude, that is, wise is the one who is contented with the spectacle of the world, which means that at a time of overwhelming social, ideological and political turbulence, the absence of historical conscience is unacceptable. Fictional discourse assumes then a restorative function, filling empty spaces, gaps and silences of historiographic discourse. In this process, one of the novelistic resources used in the transfiguration of History consists of the insertion, within the narratives plot, of 1936 newspapers texts. These articles focus on the European and Portuguese historical situation in this crucial year when authoritarian regimes of fascist character were being consolidated. The utilization of these fragments of the Portuguese press offers a detailed reconstitution of Portugals historic, social and political circumstances, thus creating a quotidian atmosphere that Ricardo Reis would have experienced in 1936.